INSTAGRAM SELFIE BEHAVIOR AS A FUNCTION OF PERSONALITY CHARACTERISTICS: A STUDY OF TURKISH EMERGING ADULTS DURING THE COVID-19 PANDEMIC - Wise, Ryan Macey; Kalkan, Aylin (Tuncay AYDEMİR, 2021)
The purpose of the current study was to investigate the relationship between personality characteristics and selfie behavior on Instagram among a sample of emerging adults in Turkey during the Covid-19 pandemic. Research has been mixed on how personality influences selfie taking and posting and demonstrates limited consideration of cultural variables, two problems we attempt to partly remedy in this study. Personality was measured using the Turkish version of the Big Five Inventory (B5KT-50-TR) and a series of questions was asked concerning frequency of selfie taking and sharing, the use of filtering and photo editing software, and the attention participants gave to monitoring followers’ ‘likes’ of their selfies. Results indicated that extraversion and openness to experience predicted the frequency of selfie sharing and monitoring of likes, while neuroticism predicted the use of filtering software. Results are contextualized within Turkish culture and related to the ongoing Covid-19 pandemic and its effects for young adults, including increased levels of loneliness.
Keywords: Selfie; Instagram; Personality; Emerging Adults; Covid-19